The 2015 STS Continuing Education Survey: A New Name for Continuing Education. - Kavita Mundle; Margaret Bean (Issues in Science and Technology Librarianship)
To keep current with the professional development needs of ACRL Science and Technology Section (STS) members, the STS Professional Development committee administers a survey approximately every two years. Surveys are sent to all section members as well as to members of the STS-L mailing list. For each survey questions are revised to reflect current topics of possible interest to section members. This article reports on the results of the 2015 survey. [ABSTRACT FROM AUTHOR]